SEED GERMINATION, LEAF COLOR, AND PLANT SEX AS MARKER TRAITS IN POLYPLOID BREEDING OF WATERMEION - alwsaif, .Warid A; Stino, .Kamal R; AbdEl-Hafez , .A.A (The Libyan Journal of Agriculture, 2023)
Six diploid varieties of watermelon and five tetrapioid varieties were crossed to produce 27 triploid progenies. The diploids we Chilean Black, Congo, Kaho, Shipper, Yellow Skin, and Yellow Elongate. The tetrapioids were Asahi-Chilean, Fumin, Ogon, and Takii’s Earliest Gem. <The percentage of seed germination, leaf color, and plant sex were studied in the triploid progeny and its parents. There were no differences in percent germination among 2x, 3x, and 4x seeds of populations having F-4 as the tetrapioid parent. Triploid-embryo seeds from the tetrapioid Fumin had the same magnitude of germination as that of the tetrapioid. Triploids originated from other tetrapioids varied in percent germination. The average percentage of germination., was from 40.0 to 93.3 in 2x, from 36.7 to 85.3 in 3x, and from 57.0 to 85.7 in 4x. As to color of leaves, the diploids Yellow Skin and Yellow Elongate possessed leaves of yellow color. The tetrapioid parents were green. The resultant triploids were light yellow, especially the mid-ribs and terminal lobes of leaves. Incomplete dominance of color genes was evident. Concerning the type of plant sex, the tetrapioid varieties were monoecious. The monoecious type was dominant over andromonoecious. Seedless Chilean watermelon.